Basal sauropodomorph locomotion: ichnological lessons from the Late Triassic trackways of bipeds and quadrupeds (Elliot Formation, main Karoo Basin) - Sciscio,Lara; Bordy,Emese M.; Lockley,Martin G.; Abrahams,Miengah (PeerJ, 2023)
Using modern ichnological and stratigraphic tools, we reinvestigate two iconic sauropodomorph-attributed tetradactyl ichnogenera, Pseudotetrasauropus and Tetrasauropus, and their stratigraphic occurrences in the middle Upper Triassic of Lesotho. These tracks have been reaffirmed and are stratigraphically well-constrained to the lower Elliot Formation (Stormberg Group, Karoo Basin) with a maximum depositional age range of <219–209 Ma (Norian). This represents the earliest record of basal sauropodomorph trackways in Gondwana, if not globally. Track and trackway morphology, the sedimentary context of the tracks, and unique features (e.g., drag traces) have enabled us to discuss the likely limb postures and gaits of the trackmakers. Pseudotetrasauropus has bipedal (P. bipedoida) and quadrupedal (P. jaquesi) trackway states, with the oldest quadrupedal Pseudotetrasauropus track and trackway parameters suggestive of a columnar, graviportal limb posture in the trackmaker. Moreover, an irregularity in the intermanus distance and manus orientation and morphology, in combination with drag traces, is indicative of a non-uniform locomotory suite or facultative quadrupedality. Contrastingly, Tetrasauropus, the youngest trackway, has distinctive medially deflected, robust pedal and manual claw traces and a wide and uniform intermanus distance relative to the interpedal. These traits suggest a quadrupedal trackmaker with clawed and fleshy feet and forelimbs held in a wide, flexed posture. Altogether, these trackways pinpoint the start of the southern African ichnological record of basal sauropodomorphs with bipedal and quadrupedal locomotory habits to, at least, c. 215 Ma in the middle Late Triassic.
Keywords: Pseudotetrasauropus; Tetrasauropus; Lesotho; Norian; Otozoum; Tetradactyl; Ichnotaxa; Maphutseng; Drag traces; Blikanasaurus